Occupational pension value in the public and private sectors - Rowena Crawford; Carl Emmerson; Gemma Tetlow (Institute for Fiscal Studies (IFS), 2010)
It is well known that in the UK defined benefit pensions are more prevalent in the public sector than in the private sector. Furthermore, we find that the average value of accrual to members of both defined benefit pensions and defined contribution pensions is lower in the private sector than in the public sector. As a result of both these factors, we find that the average value of pension accrual is much higher in the public sector than in the private sector. Due to the long-running shift away from defined benefit pensions to less generous workplace defined contribution pensions in the private sector continuing between 2001 and 2005 the difference in average pension accrual between the sectors increased over this period. While on average over this period earnings in the public sector grew 3.5% faster than in the private sector, including pension accrual increases this difference by one-third to 4.7%. We simulate a plausible reform to the public sector defined benefit pensions - an increase in the normal pension age from 60 to 65 for future pension accrual of all current members. We find that, had this reform been implemented between 2001 and 2005, average growth in total remuneration over this period in the public sector would actually have been almost the same as that in the private sector.
Keywords: J32; J38; 330; Public pensions; Age-earnings profiles; Alterssicherung; Ruhegehalt; Öffentlicher Sektor; Privatwirtschaft; Großbritannien